Private Infrastructure : A Review of Projects with Private Participation, 1990–2001 - Izaguirre, Ada Karina (World Bank, Washington, DC, 2012)
Drawing on the World Bank's private participation in infrastructure project database, this note reviews developments in 2001 and summarizes trends in 1990-2001. Data for 2001 show that total investment in projects with private participation was US$57 billion back to 1995 levels and 150 projects reached financial closure. Between 1990 and 2001, 132 low- and middle-income countries introduced private participation in infrastructure sectors 57 of them in three or four sectors. During that period the private sector took over the operating or construction risk, or both, for almost 2,500 infrastructure projects in developing countries, attracting investment commitments of more than US$750 billion. Those projects have been implemented under schemes ranging from management contracts (with or without investment commitments) to divestitures to build-operate-own or build-operate-transfer contracts for greenfield projects with merchant facilities.